V.1 - Tyler, Colin (ed.) (Bristolt, 2005)
The archives of TH Green and Edward Caird contain a large amount of material, much of it unpublished. In Green's case, the unpublished material varies greatly in both textual coherence and finish. On the one hand, Green's undergraduate essays are neatly written for the most part, and possibly for that reason all of them have now been published. The notes for the lectures that he gave as Fellow and then Whyte's Professor of Moral Philosophy at Balliol, on the other hand, are often rather chaotic, for example with two different discussions running on facing-pages of his notebooks without any immediate indication a their ended relationship. Fortunately, in many cases it is possible to disentangle these discus sions and to reconstruct the intended structure of Green's argument with a reasonable degree certainty. Nevertheless, doing so can be a long and laborious task. The situation with Edward Caird's papers is rather different. These are generally relatively complete and coherent. Unfortunately, unlike Green, Caird had appalling handwriting, , meaning that one must spend a long time deciphering Caird's manuscript before one can criticise his arguments.
Keywords: Political philosophy